2001
DOI: 10.1002/jmri.1144
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic increase in choline signal is a nonspecific marker for differentiation of infective/inflammatory from neoplastic lesions of the brain

Abstract: We report in vivo proton magnetic resonance (MR) spectroscopic findings in three benign infective/inflammatory lesions (one case each of tuberculoma, fungal granuloma, and xanthogranuloma), which showed high choline along with the presence of lipid/lactate, a feature characteristically described in neoplastic lesions. Histopathology of the lesions showed inflammatory cellular infiltrates with areas of necrosis/caseation. The spectroscopic-visible increased choline resonance in these lesions is probably the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 21 publications
4
42
0
Order By: Relevance
“…Cho/NAA, Cho/Cr ratios were the valuable tools for determining the malignancy of cranial neoplasms, used by most of the authors (3-5, 9-12, 15). In most of the former studies, both ratios increased from lowgrade to high-grade gliomas, also extremely higher in metastases and Primitive neuroectodermal tumours (PNET) (3,5,8,9,11,15). In this research, Cho/Cr ratio more than 2.5 was presented as malignant (p < 0.05) .…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Cho/NAA, Cho/Cr ratios were the valuable tools for determining the malignancy of cranial neoplasms, used by most of the authors (3-5, 9-12, 15). In most of the former studies, both ratios increased from lowgrade to high-grade gliomas, also extremely higher in metastases and Primitive neuroectodermal tumours (PNET) (3,5,8,9,11,15). In this research, Cho/Cr ratio more than 2.5 was presented as malignant (p < 0.05) .…”
Section: Discussionsupporting
confidence: 44%
“…disorders except for the cystic cranial masses, Perfusion MR and Diffusion Weighted MR imaging could also be added to MRS findings in order to get more beneficial results (2,4,7,10,16). When we look at the literature; Elevated Cho levels and reduced NAA levels had been reported in acute MS plaques and had been explained by reactive astrogliosis, inflammation and early axonal degeneration, MI at short TE was also a discriminating metabolite for the acute MS and also increased in cases of glial activation or gliosis, represented dominancy in low-grade astrocytomas related to abnormal astrocyte proliferation, nevertheless might also be seen in Encephalitis, Dementia, Epilepsy and SSPE-PML like brain disorders (1,7,10,13,14), but in high grade gliomas, metastases and more malignant tumours, its peak sharply declined (1,2,4,15,17). In our study, we had also elevated MI peaks in non-neoplastic demyelinating group.…”
Section: Resultsmentioning
confidence: 96%
“…However, some studies have found high-grade tumors (GBM) to have lower levels of Cho than grade II or III astrocytoma (57). This may be due to the presence of necrosis in high-grade tumors, because necrosis is associated with low levels of all metabolites (72 figure 5.…”
Section: Assessment Of Glioma Gradementioning
confidence: 99%
“…89 Increases in Cho due to inflammation have also been reported. 90,91 These two observations may cause some overlap in interpreting results in lesions, such as tumefactive MS, [92][93][94][95] that may have both inflammation and demyelination present.…”
Section: Cholinementioning
confidence: 99%